2008
DOI: 10.1111/j.1365-246x.2007.03705.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the induced seismicity of the Lacq gas field (Southwestern France) and model of deformation

Abstract: S U M M A R YThe goal of this paper is to propose a model of deformation pattern for the Lacq gas field (southwest of France), considering the temporal and spatial evolution of the observed induced seismicity. This model of deformation has been determined from an updating of the earthquake locations and considering theoretical and analogue models usually accepted for hydrocarbon field deformation. The Lacq seismicity is clearly not linked to the natural seismicity of the Pyrenean range recorded 30 km farther t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…In the Aquitaine basin, more than 2000 clustered local low-moderated events (M L < 4.2) were induced by the extraction of gas in the Lacq field since 1969 (Grasso and Feignier, 1990;Maury et al, 1992;Segall et al, 1994;Souriau and Pauchet, 1998;Bardainne et al, 2008). To the east of Iruña, a 4.6 mbLg magnitude earthquake was widely felt on September 18 of 2004 in an area lacking significant seismic activity in recent times.…”
Section: Induced Seismicitymentioning
confidence: 99%
“…In the Aquitaine basin, more than 2000 clustered local low-moderated events (M L < 4.2) were induced by the extraction of gas in the Lacq field since 1969 (Grasso and Feignier, 1990;Maury et al, 1992;Segall et al, 1994;Souriau and Pauchet, 1998;Bardainne et al, 2008). To the east of Iruña, a 4.6 mbLg magnitude earthquake was widely felt on September 18 of 2004 in an area lacking significant seismic activity in recent times.…”
Section: Induced Seismicitymentioning
confidence: 99%
“…For instance, Godano et al (2012) found evidence for thrust faulting induced from solution mining in the Arkema-Vauvert salt field (France), which occurred mostly along pre-existing fault structures. In addition, Bardainne et al (2008) documented dominant thrust faulting above a gas filled anticline structure in the Lacq gas field (France).…”
Section: Discussionmentioning
confidence: 99%
“…This seismicity for the period 1974-1997 has been relocated with a local 3-D velocity model (Guyoton et al 1992;Bardainne et al 2008).…”
Section: Seismicity In the Pyreneesmentioning
confidence: 99%
“…The reference is based on a NLLoc 3-D absolute earthquake location process (Bardainne et al 2008) using a flat earth approximation with simple geographic conversion to kilometres. A high resolution 3-D P velocity model (Guyoton et al 1992) and a constant V P /V S ratio of 1.73 has been used.…”
Section: Lacq Gas Field Seismicitymentioning
confidence: 99%
See 1 more Smart Citation